1993
DOI: 10.1159/000126532
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Melanocyte-Stimulating Hormone Abolishes IL-1- and IL-6-lnduced Corticotropin-Releasing Factor Release from the Hypothalamus in vitro

Abstract: Alpha-melanocyte-stimulating hormone (α-MSH) and adrenocorticotropic hormone (ACTH), peptides derived from the precursor proopiomelanocortin, share amino acid homology at the aminoterminus of ACTH, occur within the pituitary and the brain and are potent antipyretic compounds in cytokine-mediated fever. Because α-MSH and ACTH act within the hypothalamus to block leukocytic pyrogen- or cytokine-mediated fever, we hypothesized that these compounds might also be capable of blocking the action of interleukin-1 (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…On the other hand, a second array of anti-inflammatory factors such as the ·-melanocyte-stimulating hormone (·-MSH) [2,6] and the cytokine IL-10 [7,8] are also increased by LPS to diminish the action of an otherwise exacerbated immune response that might induce tissue injury and septic shock [2,3,6,[8][9][10][11][12]. Furthermore, ·-MSH not only blocks the release of a variety of proinflammatory cytokines such as IL-1 [2,3,12,13], IL-2 [13], IL-6 [2,3], IFN-Á [13] and TNF-· [2,3,12,13] but also inhibits their biological effects since it was previously shown that ·-MSH inhibited the stimulatory action of IL-1, IL-2 and IL-6 on corticotropin-releasing hormone release from incubated hypothalami [10,11]. Therefore, these and many other actions of ·-MSH support the concept that ·-MSH plays a major anti-inflammatory role [2,3,6,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a second array of anti-inflammatory factors such as the ·-melanocyte-stimulating hormone (·-MSH) [2,6] and the cytokine IL-10 [7,8] are also increased by LPS to diminish the action of an otherwise exacerbated immune response that might induce tissue injury and septic shock [2,3,6,[8][9][10][11][12]. Furthermore, ·-MSH not only blocks the release of a variety of proinflammatory cytokines such as IL-1 [2,3,12,13], IL-2 [13], IL-6 [2,3], IFN-Á [13] and TNF-· [2,3,12,13] but also inhibits their biological effects since it was previously shown that ·-MSH inhibited the stimulatory action of IL-1, IL-2 and IL-6 on corticotropin-releasing hormone release from incubated hypothalami [10,11]. Therefore, these and many other actions of ·-MSH support the concept that ·-MSH plays a major anti-inflammatory role [2,3,6,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ·-MSH not only blocks the release of a variety of proinflammatory cytokines such as IL-1 [2,3,12,13], IL-2 [13], IL-6 [2,3], IFN-Á [13] and TNF-· [2,3,12,13] but also inhibits their biological effects since it was previously shown that ·-MSH inhibited the stimulatory action of IL-1, IL-2 and IL-6 on corticotropin-releasing hormone release from incubated hypothalami [10,11]. Therefore, these and many other actions of ·-MSH support the concept that ·-MSH plays a major anti-inflammatory role [2,3,6,[10][11][12][13]. It was shown that ·-MSH inhibits the transcription factor NF-ÎB [14] that stimulates the synthesis of a variety of proinflammatory cytokines such as IL-1, IL-6 and TNF-· [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the rodent have documented effects of IL-1 on CRH in brain at multiple levels. Both IL-la and IL-ip have been reported to stimulate the release of CRH from the hypothalamus in vitro [4,5,[16][17][18], The effects of IL-1 on CRH release were blocked by inhibitors of the eicosanoid cyclooxygenase pathway but not by inhibitors of the lipooxygenase pathway [5] and appear to be independent of the histaminergic and cholinergic systems [16]. IL-1 [3 has also been shown to stimulate CRH gene expression in the paraventricular nucleus (PVN) of the hypothalamus after central or peripheral injection [3,7,19].…”
Section: Discussionmentioning
confidence: 99%
“…as well as intracerebroventricular IL-1P administration in adult rats (8)(9)(10). IL-1P is believed to stimulate either directly or indirectly the secretion of hypothalamic CRH (11)(12)(13) known to predominate in the control of pituitary corticotrophs. Intrahypothalamic IL-1P infusion as well as microlesions in the rat brain demonstrated the importance of certain brain structures (organum vasculosum of lamina terminalis, preoptic area, paraventricular nucleus) in the IL-induced stimulation of the HPAA (27,28).…”
Section: Discussionmentioning
confidence: 99%